Psychoeducation of Mental Health in Adolescents - Prisca Diantra Sampe; Rusnawati Ellis; Neleke Huliselan; Izak Jakobis Makulua (DEVOTIONIS, 2024)
Mental health is a very important issue in all human life, including adolescents. This is because adolescents in the age range of 10-19 years tend to experience a fairly high mental period. The purpose of this activity is so that teenagers will increase mental health awareness in adolescents. The implementation method is using the psychoeducational method in which there is the provision of material, discussions and presentations to adolescents. The results obtained are an increase in awareness of mental health in adolescents. Teenagers realize that mental health is important. With this activity, teenagers are moved to be better, especially in mental health issues.